Influence of hypertension on oral infections and endodontic treatment - Gomes Filho, João Eduardo [UNESP]; Martins, Christine Men [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; da Silva Santos, Ludmilla Mota [UNESP]; de Azevedo Queiroz, índia Olinta [UNESP]; Wayama, Marcelo Tadahiro [UNESP]; Yamanari, Guilherme Hiroshi; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2014)
Hypertension is characterized by peripheral vascular resistance that leads to blood pressure increase and several systemic changes that may negatively influence one's oral health. Thus, the aim of this study was to conduct a literature review on the influence of hypertension over oral conditions and endodontic treatment. Hypertension mainly affects the blood vessels, brain and kidneys. A hypertensive condition can lead to increased levels of parathyroid hormones, abnormal vitamin D metabolism, reduction in the concentration of ionized calcium and decreased calcium absorption. Therefore, hypertension can be closely associated with oral problems such as periodontal diseases, implant loss, difficulty in bone healing, reduced salivary flow and protein concentration in saliva, increased number of neutrophils and, as a consequence, favoring of inflammatory processes. It has also been suggested that the success rate of endodontic treatment in hypertensive patients is lower than in normotensive ones. The response of hypertensive patients to root canal treatment, intracanal medications and sealers should be further studied in order to provide knowledge on the changes, failures and success of endodontic treatment.
Keywords: Endodontic medicine; Endodontics; Hypertension